2005
DOI: 10.1177/0963662505052891
|View full text |Cite
|
Sign up to set email alerts
|

Conflicted scientists: the “shared pool” dilemma of scientific advisory committees

Abstract: Science advisors play a critical role in government policy making, yet these advisors are often equally attractive to regulated industry. Despite efforts to manage conflicts of interest among science advisors, allegations of conflict frequently plague advisory committee deliberations or outcomes. This article examines what we term the "shared pool" dilemma using data collected from 92 members of 11 US Food and Drug Administration advisory committees. The results suggested science advisors were generally positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Given that the participation of venture capitalists and the educational qualification of the corporate elite might affect our results [80], [65], we control for the number of venture capitalists on the board, the amount of venture capital invested and the number of senior managers and directors with JD/PhD/MD. We control for firm age since Megginson and Weiss [69] suggested that younger firms tend to have more growth options.…”
Section: Resultsmentioning
confidence: 99%
“…Given that the participation of venture capitalists and the educational qualification of the corporate elite might affect our results [80], [65], we control for the number of venture capitalists on the board, the amount of venture capital invested and the number of senior managers and directors with JD/PhD/MD. We control for firm age since Megginson and Weiss [69] suggested that younger firms tend to have more growth options.…”
Section: Resultsmentioning
confidence: 99%
“…Would-be committee experts have to disclose any income they earn from work for pharmaceutical companies, and if that income exceeds a certain amount they may be not be allowed to sit on the committee. But given that the FDA is of the opinion (together with a significant proportion of the professional worlds involved) that the most highly competent experts are also those most likely to collaborate at least sporadically with the drug industry, it has also developed a waivers procedure for such potential members (McComas 2005). This means that some proportion of AC members participating at any given meeting is likely to have financial ties with the company whose medicine is being evaluated or with a competing firm.…”
Section: B Controversies Around Conflict Of Interest In Advisory Commentioning
confidence: 99%
“…This literature has examined the expert roles and conflicts of interest of the scientific advisors who sit on these committees (McComas et al 2005;Spruijt et al 2013), the analytic approach and deliberation strategy of committees charged with conducting reviews (Dietz and Morton 2011), the contribution of scientific advisory committees to policy-making (Morton et al 2009), and the role of committees in risk assessment and risk management (Renn 1999;Walker 2002). The specific aspect of the work of these committees which is of interest in the present context is the rational processes by means of judgements and decisions about risks to human health are made.…”
Section: Expert Reasoning In Public Healthmentioning
confidence: 99%